Students' Ability to Solve Arithmetic Problems Based on APOS Theory in Cognitive Styles Differences - Eka Siti Maullina; Nining Setyaningsih (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
This study describes the ability to solve systematic problems regarding field-dependent (FD) and field-independent (FI) cognitive styles in arithmetic material. Solving systematic problems based on the APOS theory (action, process, object, schema) describes the ability of each student's cognitive style. This type of research is descriptive, using a qualitative approach. The research subjects consisted of four students consisting of two students with an FD and two FI styles in class X SMA Negeri 1 Gemolong. Data collection methods are tests and interviews. The instruments in the research were the researchers themselves, the GEFT (Group Embedded Figure Test) test as an instrument in selecting research subjects, a test of the ability to solve arithmetic problems based on APOS and interview guidelines. The analysis technique used in this study is data reduction, data presentation, and conclusion. The results showed that students with a FI cognitive style were better at problem-solving than students with an FD cognitive style. Subject FI can solve mathematical problems systematically based on APOS theory, and FI can determine methods for solving mathematical problems and originate from their thoughts not influenced by other parties. Meanwhile, FD has difficulty solving problems systematically and understanding and making mathematical models, which tends to be problematic in understanding mathematical problems and solutions that do not originate from their thinking.